RESPONSABILIDADE CIVIL DO ADVOGADO PELA PERDA DE UMA CHANCE - SOUZA, ANA JÚLIA DE OLIVEIRA DE; DALLABRIDA, CARLOS HENRIQUE MAFALDA; BOTTEGA, CAROLINE MÜLLER; BUENO, JUSTINE RATZLAFF; GATTO, LETÍCIA BARRIQUELLO; BESCHORNER, LUÍSA SARTURI; SILVA, THIAGO DOS SANTOS DA (Salão do Conhecimento, 2025)
RESPONSABILIDADE CIVIL DO ADVOGADO PELA PERDA DE UMA CHANCE